An evaluation of veterinary allergen extract content and resultant canine intradermal threshold concentrations. Issue 6 (3rd September 2018) - Abrams, Stephanie B.; Brock, Guy N.; Palettas, Marilly; Bolner, Michelle L.; Moore‐Sowers, Tricia; Plunkett, Greg A.; Cole, Lynette K.; Diaz, Sandra F.; Lorch, Gwendolen
Abstract : Background: Limited information is available for dogs on threshold concentrations (TCs), and the protein composition of common allergenic extracts produced by different manufacturers. Hypothesis/Objectives: To characterize the protein heterogeneity of tree, grass, weed and mite allergens from different lots of allergenic extracts, and to determine intradermal TCs for healthy dogs using extracts from two manufacturers. Animals: Twenty five privately owned, clinically healthy dogs and ten purpose‐bred beagle dogs. Methods and materials: Protein concentration and heterogeneity of 11 allergens from two manufacturers were evaluated using a Bradford‐style assay and SDS‐PAGE. Intradermal testing was performed with 11 allergens from each company at four dilutions. Immediate reactions were subjectively scored (0 to 4+), and objectively measured (mm) and their percentage concordance evaluated. Model‐based TCs were determined by fitting positive reactions (≥2+) at 15 min to generalized estimating equations. Results: Allergen extract protein quantity and composition varied within and between manufacturers despite sharing the same PNU/mL values. Model‐based TCs of one weed, five trees, two grasses and a house dust mite were determined for extracts from Manufacturer 1 (M1), and for extracts of three weeds, three trees and two grasses from Manufacturer 2 (M2). Receiver operating characteristic curve analyses determined a percentage concordance of the objective and subjective measurements of 77.3% for M1 and 75% for M2 allergens. Conclusions and clinical importance: Veterinary allergen extracts labelled as the same species and PNU/mL are not standardized; they show heterogeneity in composition and potency within and between manufacturers. Variability in extract content may require adjustment of intradermal testing concentrations. Abstract : Background – Limited information is available for dogs on threshold concentrations (TCs) and protein composition of common allergenic extracts produced by different manufacturers.Hypothesis/Objectives – To characterize the protein heterogeneity of tree, grass, weed and mite allergens from different lots of allergenic extracts, and to determine intradermal TCs for healthy dogs using extracts from two manufacturers.Conclusions and clinical importance – Veterinary allergen extracts labelled as the same species and PNU/mL are not standardized; they show heterogeneity in composition and potency within and between manufacturers. Variability in extract content may require adjustment of intradermal testing concentrations.